2003
DOI: 10.1016/s0002-9440(10)64314-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Erythropoietin Signaling in Squamous Dysplasia and Squamous Cell Carcinoma of the Uterine Cervix and Its Potential Role in Cervical Carcinogenesis and Tumor Progression

Abstract: Tissue hypoxia is a characteristic property of cervical cancers that makes tumors resistant to chemo- and radiation therapy. Erythropoietin (Epo) is a hypoxia-inducible stimulator of erythropoiesis. Acting via its receptor (EpoR), Epo up-regulates bcl-2 and inhibits apoptosis of erythroid cells and rescues neurons from hypoxic damage. In addition to human papillomavirus infection, increased bcl-2 expression and decreased apoptosis are thought to play a role in the progression of cervical neoplasia. Using rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
150
1
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 181 publications
(167 citation statements)
references
References 115 publications
(157 reference statements)
14
150
1
2
Order By: Relevance
“…The spatial distribution of increased Epo immunoreactivity was quite similar to that of HIF-1␣, the expression of which was also confined to tumor regions adjacent to necrotic areas, which are believed to be among the most hypoxic sites. 20 The patterns of Epo and HIF-1␣ expression were similar to those observed in cervical squamous cell carcinomas 12 and were consistent with the known regulation of Epo expression by HIF-1. 2 In contrast, EpoR expression was uniform and homogenous, although increased expression was present in tumor cells adjacent to necrotic areas.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The spatial distribution of increased Epo immunoreactivity was quite similar to that of HIF-1␣, the expression of which was also confined to tumor regions adjacent to necrotic areas, which are believed to be among the most hypoxic sites. 20 The patterns of Epo and HIF-1␣ expression were similar to those observed in cervical squamous cell carcinomas 12 and were consistent with the known regulation of Epo expression by HIF-1. 2 In contrast, EpoR expression was uniform and homogenous, although increased expression was present in tumor cells adjacent to necrotic areas.…”
Section: Discussionsupporting
confidence: 78%
“…6,12 For Epo in cytoplasm, EpoR in cytoplasm and/or the cell membrane, and ER, PR, and HIF-1␣, nuclear immunoreactivity was considered to indicate positivity. The percentage of weakly, moderately, and strongly staining cells was determined, and a staining score was calculated as follows: score (maximum, 300) ϭ 1 ϫ the percentage of weakly staining cells ϩ 2 ϫ the percentage of moderately staining cells ϩ 3 ϫ the percentage of strongly staining cells.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have hypothesised that hypoxia plays a primary role in the carcinogenesis process. Studies have shown progressively increased HIF-1a expression in breast (Bos et al, 2001), skin (Costa et al, 2001) and cervical (Acs et al, 2003) cancer development. More recently, we have shown increased expression of HIF-1a in gastric cancer development (Griffiths et al, 2007b) and in adenocarcinoma vs dysplasia in the Barrett's oesophageal cancer sequence (Griffiths et al, 2007a).…”
mentioning
confidence: 99%